Green composites: A brief review - La Mantia, F.P.; Morreale, M. (Composites. Part A, Applied science and manufacturing, 2011)
The rising concern towards environmental issues and, on the other hand, the need for more versatile polymer-based materials has led to increasing interest about polymer composites filled with natural-organic fillers, i.e. fillers coming from renewable sources and biodegradable. The composites, usually referred to as “green”, can find several industrial applications. On the other hand, some problems exist, such as worse processability and reduction of the ductility. The use of adhesion promoters, additives or chemical modification of the filler can help in overcoming many of these limitations. These composites can be further environment-friendly when the polymer matrix is biodegradable and comes from renewable sources as well. This short review briefly illustrates the main paths and results of research (both academic and industrial) on this topical subject, providing a quick overview (with no pretence of exhaustiveness over such a vast topic), as well as appropriate references for further in-depth studies.